2018
DOI: 10.1098/rsif.2017.0629
|View full text |Cite
|
Sign up to set email alerts
|

Inversion of friction anisotropy in a bio-inspired asymmetrically structured surface

Abstract: Friction anisotropy is an important property of many surfaces that usually facilitate the generation of motion in a preferred direction. Such surfaces are very common in biological systems and have been the templates for various bio-inspired materials with similar tribological properties. So far friction anisotropy is considered to be the result of an asymmetric arrangement of surface nano- and microstructures. However, here we show by using bio-inspired sawtooth-structured surfaces that the anisotropi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
38
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 60 publications
(41 citation statements)
references
References 53 publications
3
38
0
Order By: Relevance
“…The two materials varied in stiffness and were used primarily to probe the attachment ability to smooth surfaces. The saw teeth were produced by using a metal master surface as a mould (Tramsen et al, 2018). They had a base diameter of 1 mm with a height of 1.6 mm; the structures were pointed and anisotropically inclined at an angle of 60 deg.…”
Section: Substrate Preparationmentioning
confidence: 99%
“…The two materials varied in stiffness and were used primarily to probe the attachment ability to smooth surfaces. The saw teeth were produced by using a metal master surface as a mould (Tramsen et al, 2018). They had a base diameter of 1 mm with a height of 1.6 mm; the structures were pointed and anisotropically inclined at an angle of 60 deg.…”
Section: Substrate Preparationmentioning
confidence: 99%
“…The deformability of the contact partners is a significant factor influencing the true contact area and, together with the asymmetric shape of the microstructural elements, causes the anisotropic frictional properties. This, in turn, can make further contributions to the expansion of the functional properties for technical joints and devices [42][43][44].…”
Section: Discussionmentioning
confidence: 99%
“…But, through researches in recent years, scientists have found that anisotropic and variable cross‐sectional structure has better controllability. For example, Tramsen et al delved into the effects of an asymmetric surface topography, stiffness, the aspect ratio of structures, and the substrate roughness on controllability . So, the models of fiber structure with various cross section and anisotropy have gradually attracted attention, such as tapered and microwedge structure …”
Section: Introductionmentioning
confidence: 99%